Miguel Covarrubias papers - Covarrubias, Miguel, 1904-1957.; Covarrubias, Miguel, 1904-1957.; Covarrubias, Miguel, 1904-1957.
Chiefly drafts of Covarrubias's writings, notes, and notebooks pertaining to the peoples and cultures of Bali, Indonesia, and Tehuantepec, Mexico. Includes typescript drafts of his books, Island of Bali (1937) and Mexico South, the Isthmus of Tehuantepec (1946), and miscellaneous papers.
Mexican author, artist, and anthropologist.
Collection material in English, with Balinese.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anthropology -- Indonesia -- Bali Island; Anthropology -- Mexico -- Tehuantepec, Isthmus of; Balinese (Indonesian people) -- Social life and customs; Indians of Mexico -- Social life and customs; Indians of Mexico -- Mexico -- Tehuantepec, Isthmus of; Bali Island (Indonesia) -- History; Bali Island (Indonesia) -- Social life and customs; Tehuantepec, Isthmus of (Mexico) -- History; Tehuantepec, Isthmus of (Mexico) -- Social life and customs; Anthropologists; Artists; Authors